2010
DOI: 10.1016/j.ijgo.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic findings in women with pelvic organ prolapse and obstructive voiding symptoms

Abstract: Almost half of all women with advanced POP experienced incomplete bladder emptying; however, this symptom did not correlate with objective urodynamic bladder outflow tract obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
(16 reference statements)
1
9
0
Order By: Relevance
“…Some studies have demonstrated that half of all women with POP have a feeling of incomplete bladder emptying, but only 30% of the patients with advanced POP have urodynamic evidence of BOO [9,10]. Some studies tried to suggest an association between BOO and bladder trabeculation in stress urinary incontinence (SUI) patients, but there are no objective evidences of such.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that half of all women with POP have a feeling of incomplete bladder emptying, but only 30% of the patients with advanced POP have urodynamic evidence of BOO [9,10]. Some studies tried to suggest an association between BOO and bladder trabeculation in stress urinary incontinence (SUI) patients, but there are no objective evidences of such.…”
Section: Introductionmentioning
confidence: 99%
“…For the diagnosis of voiding dysfunction, some studies use only the criterion of decreased urinary flow rate (5) or just the increase in PVR criterion (6-8). Other studies use both criteria but independently of one another (11, 19), and this modifies all the results obtained. Additionally, there is another group of studies that only considers the bladder outlet obstruction diagnosis, without assessing those patients with a reduced detrusor contractility, thus having an impact on conclusions (10, 12, 20).…”
Section: Discussionmentioning
confidence: 99%
“…Anterior compartment problem of cystocele can be investigated using patient history, physical examination, transperineal US, or MRI [1]. One main shortfall of 3D EVUS for assessing stress urinary incontinence (SUI) is that meaningful dynamic imaging cannot be performed by this method due to the presence of the transducer in the vaginal canal.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic organ prolapse (POP) and pelvic floor disorders (PFD), such as voiding and defecatory dysfunction, are complex problems with varied and hotly debated empirical solutions, including traditional repairs, mesh placement, or physical therapy [1]. The lifetime risk of prolapse or urinary incontinence (UI) operation in the United States is 11-19% [2,3].…”
Section: Introductionmentioning
confidence: 99%